Analisis Pengaruh Motivasi Disiplin Kerja Dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Kecamatan Alor Barat Daya Kabupaten Alor - Karmani, Asgat Yames; Hermayanti, Hermayanti; Gorang, Alvonso Fanisius; Peny, Theresia Lounggina Luisa (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of Motivation, Work Discipline and Organizational Culture on Employee Performance at the Alor Barat Daya District Office, Alor Regency. The population of this study are Civil Servants (PNS). With the number of respondents 20 people. The sampling technique uses data collection techniques. The data analysis used is multiple linear regression analysis with the t test and f test as a tool to test the research hypothesis. The results of the study show that there is a significant influence both partially and simultaneously from the variable Motivation, Work Discipline and Organizational Culture on Employee Performance. This is evidenced by the value for the motivational variable is greater than the value, which is equal to 3,931> 1,734 with a significant value of 0.001 or 0.1% where this value is smaller than the alpha value, namely 0.05 or 5%, thus the results of this study are to accept . The value for the work discipline variable is greater than the value, which is equal to 3,086 > 1,734 with a significant value of 0.007 or 0.7%, where this value is smaller than the alpha value, which is 0.05 or 5%, thus the results of this study are accepted. The value for the organizational culture variable is greater than the value of 2,225 > 1,734 with a significant value of 0,041 or 0.41% where this value is smaller than the alpha value, namely 0.05 or 5%, thus the results of this study are accepted. The value is 86,463 and this result is greater than 3,239 with a significant value of 0,000 or 0.0% where this value is smaller than the alpha value of 0.05 or 5%, so it can be concluded that the research results accept .